Parental health, children's education and unintended consequences of state support: Quasi-experimental evidence from KwaZulu-Natal, South Africa - Anna Reuter; Till Bärnighausen; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2022)
This study investigates whether eligibility for antiretroviral therapy (ART) of HIV positive parents improved their children's educational attainment in KwaZulu-Natal, South Africa, employing a regression discontinuity design. We find that there is a positive impact of ART eligibility on paternal health, but this does not translate into general improvements of children's education. Instead, impacts differ by the previous reception of state support. Previous recipients of health-contingent state support can lose the state support after initiation of ART, as their health improves after ART is initiated. For these parents, we see a negative impact of ART eligibility on children's education, potentially driven by the negative impact on the household's wealth. In contrast, there is a positive impact of ART eligibility on children's education for fathers who previously received non-health-contingent state support.
Keywords: I12; I21; 330; Education; Health; Regression Discontinuity Design; Antiretroviral Therapy; South Africa